Historical dictionary of the Syrian uprising and civil war - Alsaleh, Asaad (Historical dictionaries of war, revolution, and civil unrest, 2021)
"Historical Dictionary of the Syrian Uprising and Civil War contains a chronology, an introduction, and an extensive bibliography. The dictionary section has more than 200 cross-referenced entries on the major events, places, and actors in the Syrian uprising"--